INCREASING EUPOPULISM AS A MEGATREND IN EAST CENTRAL EUROPE: FROM FACADE DEMOCRACIES TO VELVET DICTATORSHIPS - Ágh, Attila (Baltic Journal of Political Science, 2017)
Brexit and Donald Trump’s victory in the 2016 US presidential election has launched a wave of discussions in the international media and political science literature on “authoritarian populism” and a “populist explosion.” Although this paper also reflects on this new wave of populism in the West, it concentrates on the connections between democracy’s decline and the so-called populist explosion in eastern central Europe (ECE) and closely investigates the Hungarian case within the context of ECE. This paper describes populism in ECE as a product of the transition from fading facade democracies to emerging velvet dictatorships. These velvet dictatorships rely on the soft power of media and communication rather on the hard power of state violence. Paradoxically, the ruling anti-elite populist parties have developed a system of populism from above, managed by the new politico-business elite. Populism (social and national) and Euroscepticism are the two most basic, and twin, terms used to describe these new (semi)authoritarian regimes. Populism and Euroscepticism are convertible; they are two sides of the same coin as they express the same divergence from the EU mainstream. Therefore, this paper introduces the term: Eupopulism.